Problematika Rendahnya Mutu Pendidikan di Indonesia - Nining Sartika; Siti Rukiyah; Missriani Missriani (Journal Innovation In Education, 2023)
Education has an important role in human life. Because good education will produce good quality human resources so that with good human resources, the progress of the country will be better and develop. This research uses the literature review method. The results of this study show that the problems of education quality in Indonesia are very diverse. The problem of the quality of education in Indonesia can be seen in terms of the quality of a teacher related to teacher welfare and student achievement, education equity, and curriculum changes. Judging from the quality of teachers in Indonesia, most of whom are considered unprofessional in teaching due to inadequate teacher welfare, which has an impact on low student achievement. In terms of education equality where infrastructure facilities and equality of education play an important role in improving the quality of teachers and students, then in terms of curriculum changes that which are currently always changing following changes in the government cabinet which makes there is no definite provision in the basis of an education in Indonesia.